Faktor-faktor Berpengaruh Terhadap Keputusan Pembayaran Zakat Digital oleh Muzakki Milenial dan Gen Z di Indonesia - Seilalisa Aulia; Dewita Puspawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze religiosity, accessibility, zakat literacy, and age as influential factors on digital zakat payment decisions by millennial and gen Z muzakki in Indonesia. Data was obtained through distributing online questionnaires during November 2024 with a purposive sampling method so that 183 respondents were obtained. The population in this study are Indonesian Muslims in millennial generation (25-39 years old) and generation Z (13-24 years old). Respondents were selected based on their experience of having paid zakat either directly to the recipient (non-online) or online. Binary regression logistic was used as the test method to analyze the data. The result shows that religiosity and zakat literacy have no effect on digital zakat payment decisions. Meanwhile, accessibility and age affect the decision to pay digital zakat.